Sex-Specific Differences in the Association Between Race/Ethnicity and NAFLD Among US Population - Shaheen, Magda; Schrode, Katrina M.; Pan, Deyu; Kermah, Dulcie; Puri, Vishwajeet; Zarrinpar, Ali; Elisha, David; Najjar, Sonia M.; Friedman, Theodore C. (Frontiers in Medicine, 2021)
Non-alcoholic fatty liver disease (NAFLD) is spreading worldwide, with a racial/ethnic disparity. We examined the gender role in the racial/ethnic difference in NAFLD in the US population. We analyzed data for 3,292 individuals =>18 years old from NHANES 2017-2018, a representative sample of the non-institutionalized adult population in the US. Exclusions were subjects with elevated transferrin level, chronic hepatitis B or C, excessive alcohol use, or prescription medications that might cause hepatic steatosis. NAFLD was diagnosed by FibroScan® using controlled attenuation parameter (CAP) values: S0 <238, S1=238-259, S2=260-290, S3 >290. Data were analyzed using Chi square and multinomial regression. The overall prevalence of NAFLD was 47.9% [S2 = 16.1%, and S3= 31.8%]. The prevalence of S3 was highest among Mexican Americans (46%), lowest among Blacks (22.7%), 29.9% in other Hispanics and 32.1% in Whites (p<0.05). It was higher among Mexican American males (54.1%) compared to Mexican American females (37.7%) (p<0.05). In the adjusted model, Mexican Americans were two times more likely than Whites to have S2 and S3 (p<0.05). Only male Mexican Americans had higher odds of S2 and S3 relative to male White (p<0.05). Males had higher odds of S3 relative to non-menopausal females (p<0.05). There was no difference in the odds of S2 or S3 NAFLD among the menopausal females with or without hormone therapy relative to non-menopausal females (p>0.05). While Mexican Americans had the highest prevalence of severe NAFLD relative to the other racial/ethnic groups, only male Mexican Americans, but not females, had higher likelihood of both moderate and severe NAFLD relative to Whites. Interventions that specifically target Mexican American males are needed to increase awareness about NAFLD and its prevention.